Research methods training for national partners in Ethiopian Nile Basin rainwater management project - International Livestock Research Institute (International Livestock Research Institute, 2010)
Between 8 and 12 November 2010, the Nile Basin Development Challenge initiative (of the CGIAR Challenge Program on Water and Food - CPWF) organized a training workshop for national researchers on ‘research methods to build understanding of the planning and implementation of rainwater management strategies’ in Ethiopia. After the meeting, we talked about the workshop with Alan Duncan (ILRI), Josephine Tucker (ODI) and Eva Ludi (ODI). The workshop was part of the ‘Nile 2’ project that focuses on technologies, institutions and policies and integrated rainwater management. More information on the initiative is at https://www.ilri.org/nbdc